Cytochrome c injection induced embryo loss. (3rd September 2021) - Xu, Tonghui; Yang, Qiuhong; Wang, Banqin; Wang, Wenfu; Li, Jingxin; Ma, Yuyan; Gao, Xiaolin
Abstract: Cytochrome c has been used as first-aid in the clinic for organs which are lacking oxygen. But recent report show cytochrome c injection destroys dendritic cells (DCs) which play a pivotal role in feto-maternal tolerance. However, it is not clear whether cytochrome c injection causes abortion. The cytochrome c was injected by tail vein of mice at the Day 5.5 of pregnancy (E5.5) after mating with male BALB/c mice. The total number of implantations and resorption sites was recorded at the E12.5 in pregnant mice. Expression of interferon-γ, tumor necrosis-α interleukin (IL)-4, IL-10, IL-12 and transforming growth factor-β in the mouse endometrium was measured by ELISA. Injection of cytochrome c via tail vein at the E5.5 induced fetal resorption at E12.5, and evoked an immune imbalance at the maternal-fetal interface. Notably, injection of mouse bone marrow-derived DCs (BM-DCs) rescued the cytochrome c- evoked embryo resorption. The present study suggests cytochrome c injection causes embryo resorption in mice, hinting caution regarding the use of cytochrome c in pregnant women. In addition, it may provide an easy and novel way to establish a mouse model of abortion. Highlights: Cytochrome c injection induced fetal rejection. Cytochrome c injection leads to a T helper 1/T helper 2 imbalance at the maternal–fetal interface. A mouse model of abortion was established by injecting tail vein with cytochrome c .